2022
DOI: 10.3390/life12030449
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants as an Alternative to Control Poultry Parasitic Diseases

Abstract: Parasitic infections are a major public health concern affecting millions of people universally. This review elaborates on the potential impacts of plants and their bioactive components that have been widely used in the cure of several parasitic infections of poultry. The medicinal importance of natural herbs depends upon their bioactive ingredients, which are originated from crude plants, consequently leading to the specific action on the body. Due to the limited availability of effective drugs and high cost,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 82 publications
0
28
0
Order By: Relevance
“…Likewise, at an international level, we can find a broad application of this type of additive (e.g. [12], [24]- [28]).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, at an international level, we can find a broad application of this type of additive (e.g. [12], [24]- [28]).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Since ancient times, medicinal plants have been a tool for curing or improving diseases in humans and animals [12]. Herbs are a phytobiotic subject of studies on poultry performance and health with positive results [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars use medicinal plants to be used as animal feed additives [27]. For example, the dried and crushed above-ground parts of Houttuynia cordata can replace antibiotics, the antibacterial ability of the herb can enhance the growth performance of chickens and ducks [28], and the powder of Houttuynia cordata can be effectively used in agriculture, giving the above-ground parts a high economic value.…”
Section: Different Parts Food Value and Differential Metabolitesmentioning
confidence: 99%
“…The essential oils (EOs) distilled from aromatic plants have been confirmed to provide an effect like current therapeutic approaches, and previous studies demonstrated the reversal of obesity in Wistar rats fed high carbohydrate diets [ 10 ]. EOs have many biological properties, including antioxidant activity from having redox properties, allowing them to neutralize free radicals, and anti-inflammatory, by inhibiting the release of histamine and the activation of inflammatory mediators [ 11 , 12 , 13 , 14 ]. Recently, the effects of some compounds present in medicinal plants on adipocytes have been evaluated with a favorable effect on these cells [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], adipocyte number, and oxidative stress [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%